A foamable biodegradable bead material and foamed bead thereof

By adopting a bilayer structure of biodegradable bead material, grafting reaction of polylactic acid and temperature-sensitive polymers to improve the high-temperature melt strength, and using carbon dioxide as a foaming agent during the foaming process, the problems of easy bursting of bubble cells and hydrolyzing agents in the prior art affecting the degradation rate, achieving a foaming effect of stable structure, rapid degradation and low cost.

CN116003981BActive Publication Date: 2025-04-15NINGBO ACAD OF AGRI SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211642336.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-20
Publication Date
2025-04-15
Estimated Expiration
2042-12-20

AI Technical Summary

Technical Problem

The existing foamable polylactic acid materials are prone to burst during high-temperature foaming, resulting in poor performance, and resistant to hydrolyzing agents to affect the biodegradation rate, and are wasteful and costly.

Method used

The biodegradable bead material with a two-layer structure is a hydrolysis-resistant degradable protective shell layer, and the inner layer is a biodegradable core layer. The high-temperature melt strength is improved through the grafting reaction of polylactic acid and temperature-sensitive polymers, and carbon dioxide is used as the foaming agent during the foaming process.

Benefits of technology

The foaming effect is achieved with stable structure and good control of cell size at high temperatures, while avoiding the problem of hydrolyzing agents affecting the degradation rate, reducing material waste and cost, and improving compost degradation performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a foamable biodegradable bead material and foamable beads thereof, characterized in that: the foamable biodegradable bead material is a double-layer structure, including a degradable protective shell layer and a biodegradable core layer, the degradable protective shell layer accounts for 10-30% of the total mass of the bead; the inner biodegradable core layer accounts for 70-90% of the total mass of the bead. Compared with the prior art, the present invention has lower cost, maintains a stable structure during foaming, and has a fast degradation rate after foaming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biodegradable materials, in particular to a foamable biodegradable bead material and foamed beads thereof. Background Art

[0002] Foam materials are widely used in agriculture, transportation, packaging, medical and other fields due to their light weight, excellent thermal insulation, cushioning and sound insulation. The mainstream foam materials on the market mainly include foam resins such as foamed polystyrene, foamed polypropylene, foamed polyethylene, foamed PET, and foamed polyurethane, but most of these foam resins are non-biodegradable, and their large-scale use will cause serious ecological environmental pollution. At the same time, agricultural pollution, especially the pollution of livestock and poultry feces such as geese, is becoming increasingly serious, which seriously restricts the development of the livestock and poultry industry. With the promotion of recent environmental protection policies, the development of green and degradable foam materials is of great significance in solving material pollution and goose feces pollution.

[0003] In recent years, the demand for PLA foaming materials has been increasing year by year at home and abroad. However, in the application process, on the one hand, it is limited by its too low high-temperature melt strength. During the foaming process, the cells are easy to break, resulting in serious cell aggregation or opening. On the other hand, PLA resin is easy to hydrolyze at high temperature during the autoclave water phase foaming process, resulting in poor performance of the final foamed parts. Although the addition of a large amount of hydrolysis-resistant agent to the PLA grafting reaction can improve its degradation in the high-temperature and high-pressure foaming environment and increase its melt strength, after use, it enters the composting degradation stage. A large amount of hydrolysis-resistant agent will slow down the hydrolysis rate of PLA, hindering the biodegradation process of PLA. For example, the Chinese invention patent with patent number CN202110457816.7 (application publication number CN113372605A) "A method for preparing expandable polylactic acid composite particles with a core-shell structure, foamed beads and molded articles thereof" discloses expandable polylactic acid composite particles with a core-shell structure, wherein the shell polymer is prepared by melt blending of degradable polyester, hydrolysis resistance agent, compatibilizer, lubricant and other raw materials. Since the shell polymer is added with highly hydrophobic carbodiamine as a hydrolysis resistance agent, the stability of the foam cells can be improved, but it will affect the later composting degradation rate.

[0004] In addition, although some patents disclose polylactic acid foam beads that can be quickly degraded after use, there are still problems of material waste and high cost. For example, the Chinese invention patent "A kind of expandable polylactic acid biodegradable microparticles with a hydrolysis protection shell structure and its foaming beads" with patent number CN202010606580.4 (application publication number CN111704789A) discloses a kind of expandable polylactic acid biodegradable microparticles with a hydrolysis protection shell structure, which are gradually dissolved by the hydrolysis protection shell layer during the foaming process, thereby protecting the core layer from being hydrolyzed and having a high foaming ratio and a stable pore structure. At the same time, when the biodegradable core layer is foamed and separated from the aqueous phase dispersion system, the hydrolysis protection shell layer is just completely dissolved, revealing the easily hydrolyzed polylactic acid biodegradable core layer. However, using this method, on the one hand, it affects the input-output ratio of the material, and there is a certain amount of material waste. On the other hand, the aqueous solution after the hydrolysis of the hydrolysis protection shell layer contains small molecular weight polylactic acid resin, and the cost of wastewater treatment is high. Summary of the invention

[0005] The object of the present invention is to provide a foamable biodegradable bead material and foamed beads thereof which are cost-saving, have a stable structure during foaming, and degrade quickly after foaming.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a foamable biodegradable bead material, characterized in that: the foamable biodegradable bead material is a double-layer structure, including a degradable protective shell layer and a biodegradable core layer, the degradable protective shell layer accounts for 10-30% of the total mass of the bead; the inner biodegradable core layer accounts for 70-90% of the total mass of the bead.

[0007] Preferably, the degradable protective shell layer contains 74-94.7 parts by weight of polylactic acid resin, 5-20 parts by weight of thermosensitive polymer resin, 0.1-5 parts by weight of nucleating agent, and 0.2-1 parts by weight of lubricant, and the biodegradable core layer contains 79-98.7 parts by weight of polylactic acid resin, 1-15 parts by weight of chain extender, 0.1-5 parts by weight of nucleating agent, and 0.2-1 parts by weight of lubricant.

[0008] Preferably, the polylactic acid resin of the degradable protective shell layer and the biodegradable core layer is one or more of L-lactic acid homopolymer, D-lactic acid homopolymer, and copolymer of L-lactic acid and D-lactic acid, and the melt index of the polylactic acid resin is ≤10g / 10min under the conditions of 190°C and 2.16kg.

[0009] Preferably, the polylactic acid resin of the degradable protective shell layer and the biodegradable core layer is L-lactic acid homopolymer.

[0010] Preferably, the thermosensitive polymer resin of the degradable protective shell layer is a block polymer resin prepared by RAFT polymerization of N-isopropylacrylamide, diethyl N-acryloyl iminodiacetate and glycidyl methacrylate.

[0011] Preferably, the thermosensitive polymer resin of the degradable protective shell layer is N-isopropylacrylamide.

[0012] Preferably, the nucleating agent of the degradable protective shell layer and the biodegradable core layer is one or more of talc, calcium carbonate, kaolin, montmorillonite, zinc borate, and nano-silicon dioxide.

[0013] Preferably, the degradable protective shell layer contains 0.1-2.5 parts by weight of a nucleating agent; and the biodegradable core layer contains 0.1-2.5 parts by weight of a nucleating agent.

[0014] Preferably, the lubricant of the degradable protective shell layer and the biodegradable core layer is an amide lubricant or a stearic acid lubricant.

[0015] Preferably, the lubricant of the degradable protective shell layer and the biodegradable core layer is ethylene bisstearamide or zinc stearate.

[0016] Preferably, the chain extender of the biodegradable core layer is a mixture of one or more copolymers of isocyanate, maleic anhydride, epoxy, etc. in any proportion.

[0017] Preferably, the chain extender of the biodegradable core layer is styrene-methacrylic acid and methyl ester-glycidyl methacrylate copolymer.

[0018] Preferably, the biodegradable core layer contains 1-5 parts by weight of a chain extender.

[0019] The present invention also provides a degradable foamed bead material, which is characterized in that it is obtained by foaming the foamable biodegradable bead material in an aqueous dispersion medium.

[0020] The present invention also provides a method for preparing a degradable foamed bead material, which is characterized in that: the foamable biodegradable bead material is uniformly dispersed in an aqueous dispersion medium, carbon dioxide is introduced into an autoclave to replace air, the temperature and pressure are increased so that the carbon dioxide can penetrate into the interior of the biodegradable bead material, and after maintaining the temperature and pressure for a certain period of time, the biodegradable particles are released together with the aqueous dispersion medium into a normal temperature and pressure environment, and under the action of an instantaneous pressure difference, the high pressure inside the biodegradable beads causes them to foam and expand instantly, thereby preparing the degradable foamed bead material; the temperature of the heat preservation and pressure maintenance during foaming is 120-165°C, and the pressure is 2-6MPa; a foaming agent is used during foaming, and the foaming agent is a mixed foaming agent of one or more of carbon dioxide, nitrogen, butane, pentane, and heptane in any proportion.

[0021] Compared with the prior art, the advantages of the present invention are as follows: the foamable biodegradable bead material adopts a double-layer structure, the outer layer is a hydrolysis-resistant degradable protective shell layer, which consumes the uncapped carboxyl groups of the polylactic acid through the grafting reaction of the polylactic acid and the thermosensitive polymer, and the formed comb-shaped polymer can improve the high-temperature melt strength of the polylactic acid; the thermosensitive polymer has strong hydrophobicity in the high-temperature foaming process, which can protect the grafted polylactic acid end groups and improve the hydrolysis resistance of the grafted polylactic acid segments in high-temperature autoclave foaming. On the one hand, it avoids the problem of slowing down the degradation rate caused by the ordinary hydrophobic anti-hydrolysis agent after the polylactic acid is capped, and on the other hand, it avoids the protective effect by dissolving the protective layer, reduces material waste, does not require wastewater treatment, and reduces costs;

[0022] The degradable foamed beads obtained after foaming have good hydrophilicity at room temperature, especially at a lower temperature for composting degradation, and the thermosensitive polymer grafted with polylactic acid makes the beads easy to degrade. Therefore, when goose manure is composted, the degradation performance of the present invention is relatively high. At the same time, the bead material can be used to prepare cushioning foam products through steam molding for the transportation of livestock such as geese. DETAILED DESCRIPTION

[0023] The following examples further describe the present invention in detail.

[0024] The devices and main raw material sources used in the embodiments and comparative examples of the present invention are as follows:

[0025] Twin-screw extruder: Model SK-26, screw aspect ratio (40-52):1 Nanjing Keya Chemical Equipment Co., Ltd.;

[0026] Single screw co-extrusion equipment: model HRJSJ-35, screw length-diameter ratio is 28:1, (25-35):1 Foshan Hai Ruijia Precision Extrusion Machinery Co., Ltd.;

[0027] Polylactic acid resin:

[0028] Left-handed polylactic acid resin: S2003D, melt index 3g / 10min (190°C, 2.16kg), NaureWorks;

[0029] Right-handed polylactic acid resin: D120, melt index is 10g / 10min (190℃, 2.16kg), Total Company Left-right copolymer polylactic acid: LX975, melt index is 10g / 10min (190℃, 2.16kg), Total Company

[0030] Nucleating agent: talc AH51205L, Liaoning Aihai Talc Co., Ltd.;

[0031] Calcium carbonate KL5, Guangxi Kelong Co., Ltd.

[0032] Chain extender: SG-20, a copolymer of styrene-methacrylate, from Jiayirong Polymer (Shanghai) Co., Ltd.

[0033] Lubricant: zinc stearate, Italy Faji Co., Ltd.;

[0034] Hydrolysis resistance agent: HYADIMIDE 100, polymerized carbodiimide, Shanghai Laian Industrial Co., Ltd.

[0035] Other raw materials were commercially available and of analytical grade.

[0036] The performance characterization method of the degradable foaming material of the embodiment of the present invention and the comparative example is as follows:

[0037] Compression strength: ISO 844:2014;

[0038] Flexural modulus: GB / T 8812.1;

[0039] Density: ISO 844;

[0040] Composting test standard; ISO 14855-1.

[0041] The preparation method of the thermosensitive polymer resin of the embodiments and comparative examples of the present invention is as follows: 30g of N-isopropylacrylamide, 15g of glycidyl methacrylate, 10g of diethyl N-acryloyl iminodiacetate, 1g of 2-cyano-2-propylbenzodisulfide, and 100ml of tetrahydrofuran are placed in a 250ml three-necked flask and stirred to dissolve, the flask is continuously purged with nitrogen to replace the air in the flask, and then 0.15g of azobisisobutyronitrile is added to the flask after being heated in a water bath at 75°C for 15min, and the reaction system is sealed and reacted for 5h after nitrogen is continued to be purged for 15min. After the reaction is completed, the polymer solution is precipitated with petroleum ether to obtain a viscous polymer, which is dried to obtain a thermosensitive polymer resin.

[0042] The method for preparing a degradable foamed bead material according to the embodiments and comparative examples of the present invention comprises: uniformly dispersing a foamable biodegradable bead material in an aqueous dispersion medium, introducing carbon dioxide into an autoclave to replace air, and then increasing the temperature and pressure so that the carbon dioxide can penetrate into the interior of the biodegradable bead material; after maintaining the temperature and pressure for a certain period of time, releasing the biodegradable microparticles together with the aqueous dispersion medium into a normal temperature and pressure environment; under the action of an instantaneous pressure difference, the high pressure inside the biodegradable beads causes them to foam and expand instantly, thereby preparing a degradable foamed bead material; the temperature of the heat preservation and pressure maintenance during foaming is 120-165° C., and the pressure is 2-6 MPa; a foaming agent is used during the foaming, and the foaming agent is a mixed foaming agent of one or more of carbon dioxide, nitrogen, butane, pentane, and heptane in any proportion.

[0043] Example 1

[0044] Preparation of outer layer resin:

[0045] Weigh the raw materials according to the weight ratio, 94.7 parts of S2003D, 5 parts of temperature-sensitive polymer resin, 0.1 parts of AH51205L, and 0.2 parts of zinc stearate, put them into a high-speed mixer and mix them for 2-5 minutes, then feed them from the main feeding port of the twin-screw extruder, melt and disperse at high temperature, and extrude and granulate to obtain the outer layer resin W1.

[0046] Preparation of inner layer resin:

[0047] Weigh the raw materials according to the weight ratio, 98.7 parts of S2003D, 1 part of SG-20, 0.1 parts of AH51205L, and 0.2 parts of zinc stearate, put them into a high-speed mixer and mix them for 2-5 minutes, then feed them from the main feeding port of the twin-screw extruder, melt and disperse at high temperature, and extrude and granulate to obtain the inner layer resin N1.

[0048] Preparation of expandable biodegradable beads:

[0049] 10 parts of outer layer resin W1 and 90 parts of inner layer resin N1 were placed in two single-screw extruders for plasticization, and core-shell composite foamable biodegradable bead material was prepared by extrusion and pelletizing through a co-extrusion die head. The weight of a single foamable biodegradable bead material was controlled at 2 mg.

[0050] Preparation of degradable foamed bead material:

[0051] The above-mentioned foamable biodegradable bead material is uniformly dispersed in an aqueous dispersion medium, carbon dioxide is introduced into the autoclave to replace the air, and the temperature and pressure are increased so that the carbon dioxide can penetrate into the interior of the biodegradable bead material. After maintaining the temperature and pressure for 30 minutes, the biodegradable microparticles together with the aqueous dispersion medium are released into a normal temperature and pressure environment. Under the action of the instantaneous pressure difference, the high pressure inside the biodegradable beads causes them to foam and expand instantly, thereby preparing biodegradable foamed beads. The foaming temperature is 145°C and the foaming pressure is 3.5MPa.

[0052] Preparation of biodegradable foam products:

[0053] The prepared biodegradable foamed bead material was injected into a flat plate mold with a length of 300 mm, a width of 200 mm, and a thickness of 30 mm, and then heated by steam and cooled to form a rectangular foamed product. The obtained rectangular foamed product was subjected to a performance test.

[0054] Composting degradation test method for foam products:

[0055] A certain mass of foamed products is placed in a composting fermentation tank with a composting temperature of 28°C, a composting humidity of 60%, and a composting pH of 9.0 (simulating the alkaline environment of goose manure). The weight of the foamed products after composting for a certain period of time is measured to obtain the weight loss ratio.

[0056] Embodiment 2-5

[0057] Outer resin:

[0058] The outer layer resin was prepared according to the raw materials and amounts in Table 1. The specific preparation method is shown in Example 1.

[0059] Table 1 Amount of raw materials used to prepare the outer layer resin in each embodiment

[0060] W2 W3 W4 S2003D / wt% 74 94.7 86 Thermosensitive polymer resin / wt% 20 5 12 AH51205L / wt% 5 0.1 1.5 Zinc stearate / wt% 1 0.2 0.5

[0061] Inner resin:

[0062] The inner layer resin was prepared according to the raw materials and amounts in Table 2. The specific preparation method is shown in Example 1.

[0063] Table 2 Amount of raw materials used to prepare the inner layer resin in each embodiment

[0064] N2 N3 N4 S2003D / wt% 79 89 87 SG-20 / wt% 15 5 10 AH51205L / wt% 5 5 2.5 Zinc stearate / wt% 1 1 0.5

[0065] Degradable foam products:

[0066] The degradable foamed product was prepared according to the raw materials and amounts in Table 3. The specific preparation method is shown in Example 1.

[0067] Table 3 Raw material dosage for preparing degradable foam products in each embodiment

[0068] S1 S2 S3 S4 S5 Outer resin W1 W1 W2 W3 W4 Outer layer resin wt% 10 30 30 20 10 Inner layer resin N1 N1 N2 N3 N4 Inner layer resin wt% 90 70 70 80 90 Density g / L 43 47 52 45 42 Compression strength MPa 0.50 0.46 0.56 0.45 0.48 Flexural modulus MPa 11.6 11.5 13 11.2 12.5 Composting 365 days weight loss% 94 86 84 89 92

[0069] Example 6

[0070] The difference between this embodiment and embodiment 5 is that the polylactic acid resin used is dextrorotatory polylactic acid resin D120, and the rest is the same as embodiment 5.

[0071] Example 7

[0072] The difference between this embodiment and embodiment 5 is that the polylactic acid resin used is left-right rotating copolymer polylactic acid LX975, the nucleating agent used is KL5, and the rest is the same as embodiment 5.

[0073] Comparative Examples 1-5

[0074] Outer resin:

[0075] The outer layer resin was prepared according to the raw materials and amounts in Table 4. The specific preparation method is shown in Example 1.

[0076] Table 4 The amount of raw materials used to prepare the outer layer resin in each comparative example

[0077] W5 W6 W7 W8 W9 S2003D / wt% 74 94.7 94 64 91.5 Thermosensitive polymer resin 1 / wt% / / / 30 2.5 HYADIMIDE 100 20 5 / / / AH51205L / wt% 5 0.1 5 5 5 Zinc stearate / wt% 1 0.2 1 1 1

[0078] Inner resin:

[0079] The inner layer resin was prepared according to the raw materials and amounts in Table 5. The specific preparation method is shown in Example 1.

[0080] Table 5 Raw material dosage for preparing inner layer resin in each comparative example

[0081] N5 N6 N7 S2003D / wt% 94 74 99.9 SG-20 / wt% / 20 / AH51205L / wt% 5 5 / Zinc stearate / wt% 1 1 0.1

[0082] Degradable foam products:

[0083] The degradable foamed product was prepared according to the raw materials and amounts in Table 6. The specific preparation method is shown in Example 1.

[0084] Table 6 The amount of raw materials used in preparing the degradable foam products in each comparative example

[0085] D1 D2 D3 D4 D5 Outer resin W5 W6 W7 W8 W9 Outer layer resin wt% 30 30 20 10 10 Inner layer resin N5 N6 N7 N7 N7 Inner layer resin wt% 70 70 80 90 90

[0086] Performance Test:

[0087] The properties of the foamed products of various embodiments and comparative examples were tested according to the method of Example 1. The test results are summarized in Table 4.

[0088] Table 4 Properties of the foamed products obtained in each embodiment and comparative example

[0089] S1 S2 S3 S4 S5 S6 S7 D1 D2 D3 D4 D5 Density g / L 43 47 52 45 42 43 40 57 66 98 70 85 Compression strength MPa 0.50 0.46 0.56 0.45 0.48 0.5 0.46 0.6 0.42 0.35 0.46 0.37 Flexural modulus MPa 11.6 11.5 13 11.2 12.5 12.7 12.1 12 11 9.3 12 9.6 Composting 365 days weight loss% 94 86 84 89 92 90 94 48 55 90 75 85

[0090] It can be found from Table 4 that the outer layer resin of the material of Examples 1-7 uses a thermosensitive polymer resin and a PLA grafting reaction, so that the high-temperature melt strength of the material is higher, the dimensional stability of the foam cells is better during the foaming process, and the thermosensitive polymer has a strong hydrophobicity during the high-temperature foaming process, which can protect the grafted polylactic acid end groups from water erosion, and improve the hydrolysis resistance of the grafted polylactic acid segments in the high-temperature autoclave foaming, so as to have a lower density and a higher foaming ratio, and the mechanical properties of the parts are excellent. At the same time, the thermosensitive polymer grafted with PLA shows good hydrophilicity at room temperature, which is conducive to the swelling and erosion of water and microorganisms during the composting process, and improves its degradation performance. The weight loss ratio of the foamed parts of Examples 1-7 in the composting test is relatively high, reflecting its good degradation performance.

[0091] As can be seen from Table 6, Comparative Examples 1 and 2 use conventional hydrophobic anti-hydrolysis agents, which cannot form comb-shaped polymer segments after grafting reaction with PLA, and their high-temperature melt strength is lower than that of the thermosensitive polymer resin used in Examples 2-5, resulting in a slightly higher foaming density. Moreover, the anti-hydrolysis agent is also hydrophobic at room temperature, which will affect the degradation performance of the grafted polylactic acid resin. Therefore, the composting degradation weight loss ratio of Comparative Examples 1 and 2 is relatively low.

[0092] The foamed article of Comparative Example 3 has good degradation performance, but its outer layer resin has no hydrolysis resistance agent, and its melt strength is low and it is easy to hydrolyze during the foaming process, resulting in its final low foaming ratio and low compression and bending properties.

[0093] The outer layer resin of the material of Comparative Example 4 uses too high a content of thermosensitive polymer resin for grafting reaction with PLA, resulting in excessively high melt strength and grafting rate, which will reduce the foaming ratio and compost degradation performance.

[0094] The outer layer resin of the material of Comparative Example 5 uses a relatively low content of thermosensitive polymer resin for grafting reaction with PLA, which has low melt strength and is easily hydrolyzed during the foaming process, resulting in a low final foaming ratio and low compression and bending properties.

[0095] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. Those familiar with the art can easily make various modifications to the embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the implementation cases here, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A foamable biodegradable bead material, characterized in that: The foamable biodegradable bead material has a double-layer structure, including a degradable protective shell layer and a biodegradable core layer, wherein the degradable protective shell layer accounts for 10-30% of the total mass of the bead; and the biodegradable core layer accounts for 70-90% of the total mass of the bead; The degradable protective shell layer contains 74-94.7 parts by weight of polylactic acid resin, 5-20 parts by weight of thermosensitive polymer resin, 0.1-5 parts by weight of nucleating agent, and 0.2-1 parts by weight of lubricant, and the biodegradable core layer contains 79-98.7 parts by weight of polylactic acid resin, 1-15 parts by weight of chain extender, 0.1-5 parts by weight of nucleating agent, and 0.2-1 parts by weight of lubricant; The preparation method of the thermosensitive polymer resin is as follows: 30g of N-isopropylacrylamide, 15g of glycidyl methacrylate, 10g of diethyl N-acryloyl iminodiacetate, 1g of 2-cyano-2-propylbenzodisulfide, and 100ml of tetrahydrofuran are placed in a 250ml three-necked flask, stirred and dissolved, the flask is continuously supplied with nitrogen to replace the air in the flask, and then the flask is placed in a 75°C water bath for heating for 15min, 0.15g of azobisisobutyronitrile is added to the flask, nitrogen is continued to be supplied for 15min, the reaction system is sealed and reacted for 5h, and after the reaction is completed, the polymer solution is precipitated with petroleum ether to obtain a viscous polymer, which is dried to obtain the thermosensitive polymer resin.

2. The expandable biodegradable bead material according to claim 1, characterized in that: The polylactic acid resin of the degradable protective shell layer and the biodegradable core layer is one or more of L-lactic acid homopolymer, D-lactic acid homopolymer, and copolymer of L-lactic acid and D-lactic acid. Under the conditions of 190°C and 2.16kg, the melt index of the polylactic acid resin is ≤10g / 10min.

3. The expandable biodegradable bead material according to claim 2, characterized in that: The polylactic acid resin of the degradable protective shell layer and the biodegradable core layer is L-lactic acid homopolymer.

4. The expandable biodegradable bead material according to claim 1, characterized in that: The chain extender of the biodegradable core layer is a mixture of one or more of isocyanate, maleic anhydride and epoxy copolymers in any proportion.

5. The expandable biodegradable bead material according to claim 1, characterized in that: The chain extender of the biodegradable core layer is styrene-methyl methacrylate-glycidyl methacrylate copolymer.

6. The expandable biodegradable bead material according to claim 5, characterized in that: The biodegradable core layer contains 1-5 parts by weight of a chain extender.

7. A degradable foamed bead material, characterized in that: The foamable biodegradable bead material is obtained by foaming the foamable biodegradable bead material according to any one of claims 1 to 6 in an aqueous dispersion medium.

Citation Information

Patent Citations

  • Expandable polylactic acid composite micro-particle with core-shell structure, foamed bead and preparation method of molded piece of expandable polylactic acid composite micro-particle

    CN113372605A

  • Ink, ink cartridge, ink jet recording device, ink jet ink printed matter, compound, and composition

    CN104231744A

  • Expandable polylactic acid biodegradable particles with hydrolytic protective shell structure and foamed beads thereof

    CN111704789A